2012
DOI: 10.1161/circulationaha.111.025064
|View full text |Cite|
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus Is Associated With Faster Degeneration of Bioprosthetic Valve

Abstract: resulted in 6184 patients (mean age 71.3Ϯ5.4 years, 60.1% male) being enrolled. Of these patients, 1731 (27.9%) had type 2 DM. The propensity score-matching algorithm successfully matched 1113 patients with type 2 DM with the same number of no-DM patients. The postmatching standard differences were less than 0.1 for each of the covariates, and 64.2% of DM patients were matched. The early (30 days) mortality rate was 7.8% (nϭ87) versus 2.9% (nϭ33) in patients with or without type 2 DM (PϽ0.001), respectively. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 44 publications
1
27
0
3
Order By: Relevance
“…Type 2 diabetes mellitus has recently emerged as a significant metabolic risk factor for calcific aortic valve disease and accelerated degeneration of bioprosthetic valves. 25,26 O'Sullivan et al 27 showed increased serum OPG levels in diabetic patients. Our results suggest the impact of diabetes on the mode of calcific valve remodeling irrespectively of the OPG level.…”
Section: Clinical and Biochemical Factors Associated With Os-mentioning
confidence: 99%
“…Type 2 diabetes mellitus has recently emerged as a significant metabolic risk factor for calcific aortic valve disease and accelerated degeneration of bioprosthetic valves. 25,26 O'Sullivan et al 27 showed increased serum OPG levels in diabetic patients. Our results suggest the impact of diabetes on the mode of calcific valve remodeling irrespectively of the OPG level.…”
Section: Clinical and Biochemical Factors Associated With Os-mentioning
confidence: 99%
“…Development of robust biomarkers for disease progression will not only provide the clinical tools necessary for patient risk stratification and assessment of response to therapeutic intervention, but may also illuminate novel pathways that can be targeted medically to prevent disease progression. The need to capture this risk of disease progression is particularly acute in patients with bioprosthetic valves 6 – but may be fundamentally different from patients with native valve sclerosis 11 . The seminal realization by Demer that oxylipids and cellular ROS signals are common to both bone loss and arterial calcium accrual 141, 142 suggests that cellular and/or molecular signatures indicative of vascular and skeletal oxidative stress will prove useful.…”
Section: Future Directions: Promises and Pitfallsmentioning
confidence: 99%
“…Genetics plays a direct role in that bicuspid aortic valve – a congenital risk factor for precocious CAS – has a significant genetic diathesis 3, 4 . Recently, type II diabetes (T2DM) has emerged as a particularly relevant and worrisome metabolic risk factor for native CAVD 5 as well as precocious degeneration of bioprosthetic valves 6 . It is becoming increasingly apparent that a diverse spectrum of cell-dependent mechanisms converge to regulate valvular calcium load; this is evidenced not only in histopathologic heterogeneity of CAVD 7, 8 but also from the multiplicity of cell types –interstitial cells, endothelial cells, cardiac chondrocytes and circulating osteoprogenitors – that participate in valve biomineralization 1, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…BHV calcification has been shown to be clinically associated with young age; children and younger adults have diminished implant durations over time, with a time‐dependent increased occurrence of BHV calcification . Renal failure is an important comorbidity of SVD via calcification, and earlier BHV failure due to SVD has been observed in diabetic patients . The mechanisms responsible for SVD in the absence of calcification have been studied to a limited extent …”
Section: Introductionmentioning
confidence: 99%